Association Between Neonatal Thyroid Function and Anogenital Distance from Birth to 48 Months of Age - Luan, Min; Liang, Hong; Fang, Guanghong; Wang, Ziliang; Su, Xiujuan; Chen, Aimin; Miao, Maohua; Yuan, Wei (Frontiers in Endocrinology, 2021)
Background: Evidence from animal studies has indicated that neonatal thyroid function is vital for the reproductive development. Anogenital distance (AGD), a sensitive biomarker of the fetal hormonal milieu, measured in neonatal and childhood can be used to predict adult reproductive disorders. However, few human studies have examined the association between neonatal thyroid function and AGD. We aimed to explore their associations in a longitudinal birth cohort study. Methods: Concentrations of thyroid stimulating hormone (TSH) and thyroid hormones (THs), including total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), and free thyroxine (FT4) were measured in cord plasma in the Shanghai-Minhang Birth Cohort. The offspring AGD (AGDAP [anus–penis] and AGDAS [anus–scrotum] for boys and AGDAC [anus–clitoris] and AGDAF [anus–fourchette] for girls), body weight and anogenital index (AGI = AGD/weight [mm/kg]) were obtained at each follow-up visit. In total, 344 children (194 boys and 150 girls) with cord plasma concentrations of THs and TSH and at least one AGD measurement at birth and at 6, 12, and 48 months of age were included. Multiple linear regression and generalized estimating equation (GEE) models were used to examine the associations of cord plasma concentrations of THs and TSH with AGI. Results: Multiple linear regression models showed inverse associations of TT4, FT3, and FT4 with female AGI, although statistical significance was only reached at birth and 6 and 48 months of age. These associations were also found in GEE models: higher TT4 and FT4 concentrations were associated with lower AGIAC (TT4: β = -0.27, 95% CI: -0.50, -0.03 for middle vs. lowest tertile; FT4: β = -0.38, 95% CI: -0.61, -0.16 for middle and β = -0.30, 95% CI: -0.55, -0.04 for highest vs. lowest tertile). Besides, girls with the highest tertile of FT3 concentrations had lower AGIAF than those with the lowest tertile (the highest vs. lowest tertile: β = -0.22, 95% CI: -0.36, -0.08). Positive associations between TSH and AGI at birth and at 12 months of age were observed in boys. Conclusions: This study provides further evidence on the effects of neonatal thyroid function on reproductive development at an early life stage.